Dipeptide-catalysed Michael reaction under physiological conditions: Examination of potential bioorthogonality - Schuster, Florian; Grau, Benedikt; Xu, Huiyi; Mokhir, Andriy; Tsogoeva, Svetlana (Bioorganic & Medicinal Chemistry, 2024)
Reactions for drug synthesis under cell-like conditions or even inside living cells can potentially be used e.g., to minimize toxic side effects, to maximize bioactive compound efficacy and/or to address drug delivery problems. Those reactions should be bioorthogonal to enable the generation of drug-like compounds with sufficiently good yields. In the known bioorthogonal Michael reactions, using thiols and phosphines as nucleophiles (e.g., in C–S and C–P bond formation reactions) is very common. No bioorthogonal Michael addition with a carbon nucleophile is known yet. Therefore, the development of such a reaction might be interesting for future drug discovery research. In this work, the metal-free Michael addition between cyclohexanone and various trans-β-nitrostyrenes (C–C bond formation reaction), catalysed by a dipeptide salt H-Pro-Phe-O-Na+, was investigated for the first time in the presence of glutathione (GSH) and in phosphate-buffered saline (PBS). We demonstrated that with electron-withdrawing substituents on the aromatic ring and in β-position of the trans-β-nitrostyrene yields up to 64% can be obtained under physiological conditions, indicating a potential bioorthogonality of the studied Michael reaction. In addition, the selected Michael products demonstrated activity against human ovarian cancer cells A2780. This study opens up a new vista for forming bioactive compounds via C–C bond formation Michael reactions under physiological (cell-like) conditions.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Anticancer activity; Bioorthogonality; Glutathione; Michael addition; Peptide catalysis; Phosphate-buffered saline